Systematic identification and characterization of clinical and socio-economical correlates of granulomatous nasal and para-nasal sinuses: A large-scale study among patients of Odisha, India. Issue 9 (September 2022) - Kar, Arunima; Satapathy, Sandeep; Bepari, Kamalini; Panda, Sujata; Kar, Arundhati; Satapathy, Sambeet
Abstract: Granulomatous formation in the nose and paranasal sinuses still presents an unmet clinical challenge as it affects both the physical health and personality of patients, and the lack of a systematic diagnostic and disease management approach has further complicated the scenario. Occurrence of granulomatous nasal disorder in the rural Indian population is associated with several factors such as lack of proper medical care, lack of hygienic and clean working and living conditions, and limited financial abilities to access the already overburdened primary healthcare system. This study aims to understand the correlation disease incidence, manifestation of signs and symptoms and associated socio-epidemiological parameters for 104, 000 patients over a period of 23 months in Odisha. Primarily the study used socio-epidemiological surveys collected, annotated, and curated independently for granulomatous nasal disorder patients and compared this with their clinical records for signs & symptoms and performed several statistical analyses to better understand the disease incidence correlation with age, socio-economic and gender based parameters. Overall results suggest that males from low socio-economic background living in rural areas are the most vulnerable population and commonly affected with granulomatous nasal disorder (commonly Rhinosporidiosis sub-type) with common origin of the disease reported at the nasal septum and floor. We also highlight that change in the mass of nose followed by bleeds on touch, nasal discharge and hanging mass in throat are the most common manifestations presented by patients with granulomatous nasal disorders. Together, this research work identifies and characterise clinical and socio-economic factors that lead to and exacerbate the incidence of granulomatous nasal disorders. Abstract : Granulomatous, Nose, Paranasal sinuses, Males, Rural area, Poor living condition, Rhinosporidiosis, Fungal granuloma, Rhinoscleroma, Tuberculosis, Leprosy.